Իսլանդիայի «Կաթսաների հեղափոխությունը» և «Տնտեսական հրաշքը» - Թովմասյան, Ռուբիկ; Թովմասյան, Գայանե
В статье представлен исландский феномен или революция кастрюль, произошедшая в 2008 году в результате мирового финансового кризиса. В статье рассматриваются попытки написать новую конституцию после революции в Исландии, а также постреволюционное экономическое развитие, текущее состояние экономики и основные показатели. Анализ опыта Исландии может быть полезен для Армении с точки зрения партисипаторной демократии и экономического развития. The article presents the Iceland phenomenon or the pots and pans revolution that took place in 2008, as a result of the global financial crisis. The article reviews attempts to write a new constitution after revolution in Iceland, as well as post-revolutionary economic development, current state of the economy and key indicators. The analysis of Iceland’s practice can be useful for Armenia in terms of participatory democracy and economic development.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ